Age and mental health moderate the association between environmental concern (EC) and smoking frequency: smoking as a polluting behavior - Kang, Weixi (Frontiers in Public Health, 2023)
It is well-recognized that smoking is detrimental to the environment. However, much less is understood about smoking behavior from an environmental perspective with a focus on environmental concern (EC). The aim of this study is to establish the association between EC and smoking frequency in smokers and test whether age and mental health moderate such an association. Obtained by analyzing data using regressions on smokers (N=3, 599) from Understanding Society: the UK Household Longitudinal Study (UKHLS), which is a representative sample in the UK, the results revealed that age and mental health moderate the association between EC and smoking frequency. This association is important to understand because smoking pollutes the environment and very few studies have looked at smoking behavior from an environmental perspective.